559 Improving social media advertising campaigns for participant recruitment for clinical trials and other health research studies - Elias Samuels; Ellen Champagne; Lisa Connally; Abbey Hammontree; Anita Johnson; Shokoufeh Khalatbari; Carol F. Scott; Sue Burhop; Diane M. Harper (Journal of Clinical and Translational Science)
Objectives/Goals: This continuous quality improvement project focuses on the efficiency and effectiveness of social media campaigns for clinical trials and other health research. We analyzed data from 160 studies that recruited via social media campaigns on Meta and used the results to make improvements to MICHR’s Participant Recruitment social media campaigns. Methods/Study Population: Data on 440 ad buys purchased for Meta advertising campaigns designed for 160 studies were collected from U-M’s Research Data Warehouse, Meta, and other administrative sources. MICHR’s participant recruitment team systematically reviewed these data and rated the relevance and effectiveness of the recruitment strategies for each study. Stepwise linear regressions were used to test predictors of the efficiency and effectiveness of social media campaigns on Meta, as measured by the 1) total reach, 2) total clicks, 3) the “click-through rate,” and 4) cost per “click” of the campaign over time. Differences between the impact of campaigns for clinical trials and other clinical and translational research were found. Improvement initiatives informed by these results are underway and their impact is being evaluated. Results/Anticipated Results: 64 clinical trials and 94 non-trials were identified, with an average of $1,635 spent on social media campaigns for trials and $950 spent on non-trials. Across all social media campaigns, an average of 121,500 people were reached at a total cost of $1,220 per campaign, returning 4,288 clicks (4% click through rate) at $0.38 per click. The campaigns for trials reached more people than non-trials (152,998 vs. 101,261) and they attracted a larger number of clicks (6090 vs. 3106). The resulting average click-through rate was higher for clinical trials (4.9% vs. 3.7%), and the cost per click was lower ($0.35 vs. $0.39). Campaigns for clinical trials cost significantly more (Mean  =  $1,635, SD  =  $1,473, p  =  .020) but returned more clicks (Mean  =  6,090, SD  =  5,105, p  =  .007), and higher click-through rates (Mean  =  4.9%, SD  =  2.2%, p  =  .017). Discussion/Significance of Impact: There is great variation in the efficiency and effectiveness of social media advertising campaigns for recruitment into clinical trials and other clinical and translational studies. While the size and cost of these campaigns were found to be higher for clinical trials than for non-trials, the effectiveness of trials’ campaigns can also be greater.